Studi Tingkat Kerusakan Akibat Serangan Hama pada Meranti Merah (Shorea Leprosula Miq.) di Areal Persemaian IUPHHK-HA Dwima Group Kabupaten Katingan: Study on the Level of Damage Due to Pest Attacks on Red Meranti (Shorea Leprosula Miq.) in the Seedling Area of IUPHHK-HA Dwima Group, Katingan Regency - Miyasih, Miyasih; Firdara, Eritha Kristiana; Putir, Patricia Erosa; Nuwa, Nuwa; Toni, Hendra (Jurusan Kehutanan, Fakultas Pertanian Universitas Palangka Raya, 2023)
The objectives in this study are: 1. Identify and describe the types of pests that attack red meranti seedlings (Shorea leprosula Miq.) in the IUPHHK-HA Dwima Group seedling area; 2. Know and categorize the level of damage caused by pest attacks on red meranti seedlings (Shorea leprosula Miq.) in the IUPHHK-HA Dwima Group seedling area. Sampling is done by simple random sampling. Random sampling was taken from 5 beds containing 5000 red meranti seeds, in each bed there are 100 red meranti seedlings that will be used as research objects. There are 3 types of pests that attack red meranti seedlings, namely black ants (Lasius niger), spiders (Phintella vitatta) and caterpillars (Doleschallia bisaltide). Spider pests with damage intensity of 3.12% and attack area of 10.8%; black ants with a damage intensity of 2.56% and an attack area of 10%, and caterpillars with a damage intensity of 2.6% and an attack area of 6%. The degree of pest damage belongs to the category of mild infestation. The intensity of damage to each bed belongs to the light category with an average of 11.8% while the average value of attack area is 26.8% belonging to the moderate attack category.